Epstein-Barr virus coinfection in cerebrospinal fluid is associated with iIncreased mortality in Malawian adults with bacterial meningitis - Kelly, Matthew J.; Neuhann, Florian (The journal of infectious diseases, 2012)
Abstract. Mortality from adult bacterial meningitis exceeds 50% in sub-Saharan Africa. We postulated that—particularly in individuals infected with human immun